PERAN USAHA MIKRO, KECIL DAN MENENGAH DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DESA JONGKONGKIRI TENGAH PERSPEKTIF EKONOMI ISLAM - Herry Ardiyansyah (BORJUIS: JURNAL OF ECONOMY, 2023)
In order to fulfill life's needs in order to be prosperous, people who have the ability and are keen to see their own potential and are able to identify the environment, can find opportunities and open up business opportunities for the community. Efforts made to fulfill living needs include micro, small and medium enterprises (MSMEs). The existence and survival of micro, small and medium enterprises is also influenced by internal factors, namely economic motives and external factors, namely the environment and economic habitat in which a person or a community lives in carrying out its economic life. With the role of Micro, Small and Medium Enterprises around Jongkong District, it can indirectly overcome the problem of unemployment in Jongkong Kiri Tengah Village, especially Jongkong District and have an impact on the level of economic welfare of the community. This research uses qualitative research with a descriptive approach. The object of this research is Fish Crackers which is a micro, small and medium enterprise in the area. Data collection techniques and tools through interviews, observation and documentation. Data analysis includes data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that micro, small and medium enterprises in Jongkong Kiri Tengah Village are experiencing positive development, both from the number of Small and Medium Enterprises increasing or from the community's income becoming better. the role of micro, small and medium enterprises in Jongkong Kiri Tengah village through the fish cracker MSME business, namely: a) having the same method in managing fish crackers, b) making crackers is done traditionally with several stages, namely preparing ingredients, making dough, steaming/boiling, cutting crackers, drying/drying and packaging/packing. c) improving community welfare, including reducing the number of unemployed in Jongkong Kiri Tengah Village. d) the role of Micro, Small and Medium Enterprises in increasing people's income in Jongkong Kiri Tengah Village from an Islamic Economics perspective, namely having benefits for the lives of many people to fulfill their needs for worship, food, drink, clothing, shelter and other things which are a form of maintaining the soul of the community.